Pravice in obveznosti po novi delovni zakonodaji - Belopavlovič, Nataša (Podjetje in delo, 2013)
The author presents the main novelties in the field of rights and obligations brought by the new Slovenian Employment Relationship Act (ZDR-1). The focus is on simplifications concerning conclusion and termination of employment relationship, new provisions on notice periods and severance pays, novelties concerning the determination and use of annual leave and special protection of economically dependent workers.
Keywords: delovna razmerja; delovno pravo